FAKTOR RISIKO KEJADIAN COVID-19 DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN INDRAGIRI HILIR TAHUN 2022 - Arman Arman; Mitra Mitra; Oktavia Dewi; Musfardi Rustam (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The increase in COVID-19 cases in the community is caused by the rapid spread of the virus. In Indonesia, 6,051,532 cases were recorded and Riau Province was in 10th position with 150,450 cases. In Indragiri Hilir Regency, the number of positive confirmed cases is 6,221 cases, an increase from 2020 to 2021. This study aims to determine the risk factors for the occurrence of Covid-19 in the Work Area of the Health Service of Indragiri Hilir Regency in 2022. This study used an observational analytic quantitative approach with a cross sectional study design. This research was conducted in the working area of Indragiri Hilir Regency in July 2022. Data analysis was carried out univariate, bivariate and multivariate using multiple logistic regression test. Based on the results of the study, it is known that the variables that influence the incidence of COVID-19 are vaccination with a significant value of 0.001 (POR: 155.527; 95% CI: 16,327-1481,527), education with a significant value of 0.001 (POR: 95,073; 95% CI: 10,579 -854,453), occupation with a significant value of 0.001 (POR: 12.703; 95% CI: 3.808-42.378), comorbidity with a significant value of 0.004 (POR: 17.785; 95% CI: 2.445-129.353). Variables that affect the incidence of COVID-19 are age, gender and contact history. The most dominant factor with the incidence of Covid-19 in the Work Area of the Indragiri Hilir District Health Office in 2022 is vaccination status. For people who have been infected with COVID-19, they should immediately check with health service facilities and immediately receive medical treatment, and for people who have not been infected with COVID-19, always apply a healthy lifestyle and comply with health protocols.